PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWAKELAS VIII SMP NEGERI 14 MERANGINTAHUN PELAJARAN 2022/2023 - Anggun Lilis Hildawati; Yohanes; Sukur (Pendidikan Matematika | Universitas Merangin, 2024)
This study was conducted to explain students' ability to solve mathematical problems in Class VIII through problem-based learning (PBL) simulation in SMP Negeri 14 Merangin during the 2022/2023 school year. I did it. This training has proven to be better than traditional teaching methods. We use an experimental approach with a quantitative approach and a post-test study design. The subjects of this studys were all Grade VIII students of SMP Negeri 14 Merangin for the 2022/2023 school year, a total of 67 students. All samples were from experimental class VIII A and control class VIII B. In the study, the researchers used a simple random sampling technique. Testing is used as a data collection method and t-test is used as a data analysis method. Analysis of the data shows that the mean score of students in the sample class using the problem-based learning model is 14.08, while the mean score of the control class is 12.45. Therefore, based on the hypothesis result, tcount is greater than ttable which is 2.3582≥1.6802 at a significance level of 0.05, then Ho is rejected. High is acceptable. The conclusion of this study is that the mathematical problem solving ability of SMP Negeri 14 Merangin VIII students studying using a Problem-Based Learning (PBL) model in the 2022/2023 academic year is significantly lower than that of students studying using traditional teaching methods. In other words, they were better than the students who were given the test.